Analisis Kinerja Keuangan Pada PT. Bank Pembangunan Daerah Sumatera Selatan dan Bangka Belitung - Oktalia Rengganis; Reva Maria Valianti; Oktariansyah Oktariansyah (Universitas PGRI Palembang, 2020)
ABSTRACT The data observed in this study are financial statements in the form of financial position reports and income statements from 2011 to 2015. Data analysis and discussion were carried out using quantitative descriptive analysis methods and qualitative approaches, namely by analyzing risk profile, earnings and capital. The results of this study indicate that the LDR level of PT. Bank Sumsel Babel, namely in 2011 and 2012 amounted to 76% and 77% <85% in 2013 and 2014 at 95% and 89% <100% In 2015 the LDR (Loan To Deposit Ratio) was 101% <120%. The NPL (Non Performing Loan) Ratio of Bank Sumsel Babel in 2011 was 1.5% <2% in 2012 and 2014 amounted to 6.9% and 7.6 <8% in 2013 amounted to 9%> 8% in 2015 by 4.4% <5%. BOPO Ratio (Operational Cost to Operational Income) Bank Sumsel Babel in 2011, 2012, 2013, 2014 and 2015 was 81%, 84%, 86%, 82% and 81% <90%. The ROA (Return on Assets) ratio of Bank Sumsel Babel in 2011, 2012, 2013, 2014 and 2015 was 2%, 2%, 2%, 2% and 3%> 2%. The ROE (Return on Equity) ratio of Bank Sumsel Babel in 2011 was 26%> 20%. whereas in 2012, 2013, 2014 and 2015 it was 18%, 13%, 16% and 17% <20%. The CAR (Capital Adequacy Ratio) of Bank Sumsel Babel in 2011 and 2012 was 12% and 14% <15%. Whereas in 2013, 2014 and 2015 amounted to 15%, 18% and 20%> 15%. So it can be interpreted that the level of liability of PT Bank Sumsel Babel is considered not good. because the level of the NPL ratio is high, this means that the company has not been able to utilize its funds effectively and efficiently. Keywords: Loan To Deposit Ratio, Non Performing Loan, BOPO, Return On Assets, Return On Equity, Capital Adequacy Ratio. ABSTRAK Data yang diamati pada penelitian ini merupakan laporan keuangan berupa laporan posisi keuangan dan laporan laba rugi dari tahun 2011 sampai tahun 2015. Analisis data dan pembahasan dilakukan dengan menggunakan metode analisis deskriptif kuantitatif dan pendekatan kualitatif yaitu dengan menganalisis risk profile, earnings dan capital. Hasil penelitian ini menunjukkan bahwa tingkat LDR PT. Bank Sumsel Babel yaitu pada tahun 2011 dan 2012 sebesar 76% dan 77% < 85% pada tahun 2013 dan 2014 sebesar 95% dan 89% < 100% Pada tahun 2015 Rasio LDR (Loan To Deposit Ratio) sebesar 101% < 120%. Rasio NPL (Non Performing Loan) Bank Sumsel Babel pada tahun 2011 sebesar 1,5% < 2% pada tahun 2012 dan 2014 sebesar 6,9% dan 7,6 < 8% pada tahun 2013 sebesar 9% > 8% pada tahun 2015 sebesar 4,4% < 5%. Rasio BOPO (Biaya Operasional Pendapatan Operasional) Bank Sumsel Babel pada tahun 2011, 2012, 2013, 2014 dan 2015 sebesar 81%, 84%, 86%, 82% dan 81% < 90%. Rasio ROA (Return On Assets) Bank Sumsel Babel pada tahun 2011, 2012, 2013, 2014 dan 2015 sebesar 2%, 2%, 2%, 2% dan 3% > 2%. Rasio ROE (Return On Equity) Bank Sumsel Babel pada tahun 2011 sebesar 26% > 20%. sedangkan pada tahun 2012, 2013, 2014 dan 2015 sebesar 18%, 13%, 16% dan 17% < 20%. Rasio CAR (Capital Adequacy Ratio) Bank Sumsel Babel pada tahun 2011 dan 2012 sebesar 12% dan 14% < 15%. Sedangkan pada tahun 2013, 2014 dan 2015 sebesar 15%, 18% dan 20% > 15% Maka dapat diartikan bahwa tingkat liability PT Bank Sumsel Babel dinilai belum baik. karena tingkat rasio NPL tinggi, hal ini berarti perusahaan belum dapat memanfaatkan dananya secara efektif dan efisien. kata kunci : Loan To Deposit Ratio, Non Performing Loan, BOPO, Return On Assets, Return On Equity, Capital Adequacy Ratio.